2015
DOI: 10.1007/s11540-015-9303-7
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Potato Model: LINTUL-POTATO-DSS

Abstract: In 1994, LINTUL-POTATO was published, a comprehensive model of potato development and growth. The mechanistic model simulated early crop processes (emergence and leaf expansion) and light interception until extinction, through leaf layers. Photosynthesis and respiration in a previous crop growth model-SUCROSwere substituted by a temperature-dependent light use efficiency. Leaf senescence at initial crop stages was simulated by allowing a longevity per daily leaf class formed, and crop senescence started when a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 20 publications
0
32
0
6
Order By: Relevance
“…However, usually a more dynamic approach is used, including the modelling of leaf appearance, expansion of the leaf area and senescence. Another difference between models is whether they describe the development of separate individual leaves, or handle the whole canopy as one "big leaf" (Kabat et al 1995;Raymundo et al 2014;Haverkort et al 2015).…”
Section: Leaf Areamentioning
confidence: 99%
See 2 more Smart Citations
“…However, usually a more dynamic approach is used, including the modelling of leaf appearance, expansion of the leaf area and senescence. Another difference between models is whether they describe the development of separate individual leaves, or handle the whole canopy as one "big leaf" (Kabat et al 1995;Raymundo et al 2014;Haverkort et al 2015).…”
Section: Leaf Areamentioning
confidence: 99%
“…Their conclusion was that (when calibrated) the simple model could predict the yield equally well as the complex model (when calibrated), despite a much lower input data requirement. Another example can be seen in the long term evolution of the LINTUL-POTATO model, as described by Haverkort et al, (2015). Already in the original version of this model (Kooman and Haverkort, 1994), some simplifications were made from its predecessor, the SUCROS crop growth model.…”
Section: Future Perspectives: Application Of the Models In Precision mentioning
confidence: 99%
See 1 more Smart Citation
“…The simple crop growth model LINTUL-DSS (Haverkort et al 2015a) is used to calculate the attainable yield. This simple model calculates dry mass production through the interception of radiation by green leaves.…”
Section: The Lintul-dss Modelmentioning
confidence: 99%
“…Therefore, simulation models could potentially also be useful to help improve yield forecasts for the potato processing industry. LINTUL-Potato-DSS is an example of such a model that has been successfully calibrated and validated for different potato production environments around the world (Kooman and Haverkort 1995;Caldiz et al 2001;Franke et al 2011;Haverkort et al 2015). Haverkort et al (2015) showed how to use the LINTUL-Potato-DSS model to forecast yield anytime during the growing season by using real time weather data until the current day in the season and long term historical weather data to forecast the yield at any future date.…”
Section: Introductionmentioning
confidence: 99%